Estimation of water erosion rates in Espírito Santo state, Brazil - Elias de Miranda Teodoro, Alexandre; Henrique Expedito Lense, Guilherme; Ernesto Bernardes Ayer, Joaquim; Luiz Mincato, Ronaldo (Revista Ciência Agronômica, 2023)
Water erosion is a natural geological process that is common in tropical regions. It is important to monitor it tocontain its physical, environmental, and socio-economic impacts. In the Espírito Santo state, Brazil, much of the land is used foragriculture and studies related to water erosion are scarce. The spatial modeling of water erosion is useful for proposing mitigatingmeasures because combining it with data from geographic information systems can identify the areas most prone to soil loss. TheRevised Universal Soil Loss Equation - RUSLE, is a model that requires little input data and is easy to use, providing results usefulof helping to mitigate water erosion and promote sustainable land use planning. This study estimates the water erosion rates in theEspírito Santo state by RUSLE and compares them with the soil loss tolerance (T) limits. The parameters used in the model are theland use and management, the soil attributes, the relief and the climate factors. Approximately 38.65% of the state’s area shows soilloss above the T limit (7.79 - 14.14 Mg ha-1 year-1). The areas with steeper slopes and low vegetation cover have most of the highesterosion rates. The mean annual soil loss of the entire state is 33.55 Mg ha-1 year-1. RUSLE provided a diagnosis useful of directingerosion mitigation measures to the most susceptible areas, enabling sustainable planning to support the state’s socio-economic development.